Transformation of National Tourism in Blitar City: SOAR Approach in Realizing Smart Tourism City - Natan Waskito Firtanto; Titik Poerwati; Tjokorda Nirarta Samadhi; Kevie Desderius; Degihon Daud Martua Hutabarat; Yoanda Alif Ya Rizqullah Sahadevi; Nadia Trikarlina Laraswati (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This research aims to identify and formulate strategies for developing Blitar City's national tourism destinations through SOAR analysis and geomarketing approaches to support the realization of a smart tourism city that harmoniously integrates modern technology with strong local wisdom and national heritage values. Method: This study employs a qualitative design with a multidisciplinary approach, utilizing SOAR (Strengths, Opportunities, Aspirations, Results) analysis as the primary analytical framework. Data collection was conducted through field observations, in-depth interviews with key stakeholders including the Tourism Office, tourism business actors, and local communities, complemented by secondary data from government policies and previous studies. The research specifically focuses on national tourism destinations in Blitar City and applies geomarketing principles for strategic tourism route development. Result: The SOAR analysis revealed strategic priorities with the Opportunity-Result (OR) strategy scoring highest (9.36), followed by Opportunity-Aspiration (OA) strategy (9.05). Key findings include the identification of Blitar's strong national tourism identity centered on Bung Karno's heritage, strategic opportunities through smart tourism city trends and government support, and the formulation of a three-pillar Smart Tourism City framework encompassing smart infrastructure, smart tourist experience, and smart destination governance. The study proposes geomarketing-based integrated heritage tourism trails and dynamic visitor flow management systems. Contribution: This research advances smart tourism theory by demonstrating the successful integration of SOAR analysis with geomarketing approaches specifically for heritage tourism destinations. It contributes new knowledge by providing a contextually-adapted smart tourism city framework that preserves national identity while embracing technological innovation. The study offers practical value to policymakers, tourism managers, and stakeholders by delivering evidence-based strategies for transforming traditional heritage destinations into competitive smart tourism cities, serving as a replicable model for similar national heritage tourism destinations in Indonesia and globally.